How Do Leaders Influence Innovation and Creativity in Employees? The Mediating Role of Intrinsic Motivation. Issue 9 (October 2021) - Siyal, Saeed; Xin, Chunlin; Umrani, Waheed Ali; Fatima, Seerat; Pal, Debajyoti
Drawing on social exchange theory, this research examines how inclusive leaders foster innovative work behavior and creativity in employees. Data were collected in two steps from the 320 employees working in Chinese R&D organizations to draw the result for this research. The findings indicate a positive impact of inclusive leadership on innovative work behavior and creativity. In addition, intrinsic motivation mediates this relationship. The implications and future research are also discussed.